Perlindungan Hak Pengguna dalam Praktik Pengolahan Data oleh Platform TikTok sebagai Penyelenggara Sistem Elektronik Privat: Analisis dalam Perspektif Hukum Teknologi Informasi - A, Amelia; Nurkhaerani, Ema (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The development of the TikTok platform as a private Electronic System Operator (PSE) with 157.6 million Indonesian users has triggered a massive increase in the processing of personal data. This study analyzes the forms of protection of TikTok users' rights based on Law Number 11 of 2008 concerning Electronic Information and Transactions (amended by Law Number 1 of 2024), Law Number 27 of 2022 concerning Personal Data Protection, and Government Regulation Number 71 of 2019 concerning the Implementation of Electronic Systems and Transactions, as well as legal sanctions for violations of data transparency and accountability. This study uses a normative juridical method, and the results show comprehensive protection through the rights of access, correction, data deletion, and age verification for children, supported by gradual sanctions ranging from administrative to criminal imprisonment and fines of billions of rupiah. The precedent of TikTok's TDPSE suspension by Komdigi in October 2025 proves effective enforcement. The study recommends strengthening audits, independent supervisory agencies, and data localization for large PSEs to reinforce Indonesia's digital sovereignty.